2017
DOI: 10.1038/emm.2017.15
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of glutathione metabolism attenuates esophageal cancer progression

Abstract: Esophageal squamous cell carcinoma (ESCC) is a deadly malignancy with regard to mortality and prognosis, and the 5-year survival rate for all patients diagnosed with ESCC remains poor. A better understanding of the biological mechanisms of ESCC tumorigenesis and progression is of great importance to improve treatment of this disease. In this study, we demonstrated that the glutathione metabolism pathway is highly enriched in ESCC cells compared with normal esophageal epithelial cells in an in vivo mouse model.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 32 publications
0
16
0
Order By: Relevance
“…Therefore, one might consider exploring different routes of BSO administration to avoid an invasive procedure and the risk of inducing a potentially fatal haemorrhage in highly vascularized tumours. An efficient reduction of tumour burden has, for instance, been shown in an animal model of oesophageal cancer, where BSO was dissolved in drinking water at a concentration of 20 mM [ 55 ]. In an orthotopic glioma model, a reduction of tumour glutathione to about 8% of the non-treated control values was achieved by a combination of intraperitoneal and oral BSO administration [ 14 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, one might consider exploring different routes of BSO administration to avoid an invasive procedure and the risk of inducing a potentially fatal haemorrhage in highly vascularized tumours. An efficient reduction of tumour burden has, for instance, been shown in an animal model of oesophageal cancer, where BSO was dissolved in drinking water at a concentration of 20 mM [ 55 ]. In an orthotopic glioma model, a reduction of tumour glutathione to about 8% of the non-treated control values was achieved by a combination of intraperitoneal and oral BSO administration [ 14 ].…”
Section: Discussionmentioning
confidence: 99%
“…The results of at least two Phase I clinical trials in which BSO was administered intravenously as adjuvant therapy in patients with solid malignant tumours have been published [ 55 , 56 ]. An intracellular GSH depletion to about 30–40% of the baseline levels was induced, resulting in a significant inhibition of y-glutamylcysteine synthetase, the rate-limiting enzyme of GSH synthesis [ 58 ].…”
Section: Discussionmentioning
confidence: 99%
“…The dosage of Ori was comparative to our experiment, specifically, Ori (27 μM) significantly reduced GSH in esophageal cancer TE1 cells. Importantly, Peng et al showed that glutathione metabolism was among the top enriched pathways in ESCC (Esophageal squamous cell carcinoma) through studies on ESCC mice, suggesting that inhibition of glutathione metabolism may be an effective strategy for ESCC therapy (Peng, Linghu, & Chen, 2017). As mentioned before, lipid peroxidation is the essential feature of ferroptosis, thus dysregulation of GSH synthesis and metabolism would like to induce ferroptosis in ESCC.…”
Section: Discussionmentioning
confidence: 99%
“…All values presented as mean ± SD (n = 3 for each group). Statistical differences were calculated by one-way ANOVA: ***p < .001; **p < .01 vs. 0 hr group [Colour figure can be viewed at wileyonlinelibrary.com] inhibition of glutathione metabolism may be an effective strategy for ESCC therapy (Peng, Linghu, & Chen, 2017). As mentioned before, lipid peroxidation is the essential feature of ferroptosis, thus dysregulation of GSH synthesis and metabolism would like to induce ferroptosis in ESCC.…”
Section: Discussionmentioning
confidence: 99%
“…For example, auranofin has shown to decrease the expression of NF-kB, thereby overcoming acquired therapy resistance [70,71]. Similar effects were obtained when inhibiting GSH metabolism [72]. However, it should be mentioned that the activation of NF-kB is also responsible for inflammatory responses, which can induce cross-presentation of tumor antigens and stimulate antitumor immune responses [73].…”
Section: Combinations Of Different Oxidative Stress-inducing Therapiesmentioning
confidence: 90%